Nuss Technique for Pectus Excavatum in Adult Patients: Cosmetic Satisfaction and Improvement of Quality of Life in a Single-Center Experience - Viggiano, Domenico; Bongiolatti, Stefano; Borgianni, Sara; Lo Piccolo, Roberto; Voltolini, Luca; Gonfiotti, Alessandro (Frontiers in Surgery, 2022)
Objectives Since its introduction, Nuss minimally-invasive procedure for Pectus Excavatum (PE) repair (MIRPE) has become the method of choice. The current study describes our experience of PE correction in adults, with particular focus on post-operative outcomes, pain, quality of life and patients’ satisfaction. Methods We enrolled for this observational study n=93 adult patients from 2011 to 2018. The Haller index was used to quantify PE severity. Pulmonary function tests and cardiac examinations were performed preoperatively; we developed a standardized surgical technique and post-operative treatment, including follow-up at 3, 12 and 24 months after surgery and 6 months after bar removal. We also evaluated the Quality of life and the satisfaction with the cosmetic result after procedure with standardized questionnaires. Results No operative or perioperative deaths occurred nor life-treating complications. 13 complication occurred in 12 patients, with a total complication rate of 14% (n=13/93). Pain intensity decreased in the follow-up [pain score visual analogue scale (VAS) at 3 months: median 1 (0-8), 12 months: median 1 (0-5), 24 months: median 1 (0-4)]. Better or much better quality of life after the Nuss procedure was observed: n = 79 (84.1%) at 3 months, n = 80 (86%) at 12 months and n = 85 (91.4%) at 24 months. After 2 years of observation, over 90% of patients described improvement in their quality of life and satisfaction with the cosmetic results. Only a very small group of patients suffered from pain in the follow-up. Conclusion Our results demonstrate that the MIRPE procedure is safe and can be performed with excellent results in adults both for improvement of quality of life and for satisfaction with cosmetic results.